2015
DOI: 10.3109/01658107.2015.1016579
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Ophthalmological Findings in Children and Adolescents with Chronic Ataxia

Abstract: Chronic ataxia is a challenging problem in paediatric neurology. It is caused by a multitude of disorders that at least initially have similar or non-specific phenotype. Some of these disorders have associated neuroophthalmological signs (N-OS). The aims of this study are to describe the N-OS and their frequencies in general and by disease aetiology in paediatric patients with chronic ataxia. The authors identified 184 patients under age 17 years with chronic ataxia (42 months duration or recurrent) during 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…6/11 individuals of the cohort showed increased tone and/or asymmetric movement patterns that largely resolved during childhood, including significant infantile dystonia in P9. Strabismus is seen in 84% of the previously published individuals we reviewed [1e3, 7,8,10,12,13] and 82% of individuals reported in this study, whereas in a series of pediatric patients with different chronic ataxias, only 29% exhibited strabismus [23].…”
Section: Discussionmentioning
confidence: 61%
“…6/11 individuals of the cohort showed increased tone and/or asymmetric movement patterns that largely resolved during childhood, including significant infantile dystonia in P9. Strabismus is seen in 84% of the previously published individuals we reviewed [1e3, 7,8,10,12,13] and 82% of individuals reported in this study, whereas in a series of pediatric patients with different chronic ataxias, only 29% exhibited strabismus [23].…”
Section: Discussionmentioning
confidence: 61%
“…Oculomotor apraxia is a highly suggestive symptom of cerebellar malformation also in toddlers and older children. Saccadic initiation failure is the most common eye movement abnormality, being saccades hypometric or absent ( Tusa and Hove, 1999 ; Salman and Chodirker, 2015 ). Furthermore, more complex abilities, such as tandem gait or finger-nose and heel-shin tests, cannot be examined before 4 years of age or according to the cooperation skills of the child.…”
Section: Age-related Cerebellar Examinationmentioning
confidence: 99%
“…Strabismus is frequent in JS, as in other diseases associated with non-progressive cerebral or cerebellar abnormalities [113], and in one small series it was the most common neuro-ophthalmologic abnormality [113]. It can present as horizontal or vertical misalignment, esotropia or exotropia, fixed or alternating, but most often it presents as elevation of the abducting eye and depression of the adducting eye in lateral gaze [8,9,10,21,76,80,95,114,115].…”
Section: Ocular Colobomasmentioning
confidence: 99%
“…In a study of neuro-ophthalmological findings in pediatric patients with chronic ataxia, it was found that diseases associated with non-progressive cerebral or cerebellar abnormalities like JS and related disorders were associated with high prevalence of strabismus. Four out of five of the patients with JS surveyed displayed neuro-ophthalmologic features, the most common feature being strabismus [113].…”
Section: Ocular Colobomasmentioning
confidence: 99%